The clock is ticking - Zawawi, Dahlia; Johari, Juliana (Universiti Putra Malaysia Press, 2009)
This case mainly on talent management and training issues, presents an opportunity for post graduate and undergraduate students to test their knowledge on a real life situation. It provides critical information on the organization’s internal and external environment and highlight issues that require students’ immediate attention. This case has a moderate level of difficulty and may be used in the relevant management classes such as Human Resources and Organizational Behavior.